Efficacy and treatment costs of zoledronate versus pamidronate in paediatric osteoporosis. Issue 1 (7th October 2017) - Saraff, Vrinda; Sahota, Jaskiran; Crabtree, Nicola; Sakka, Sophia; Shaw, Nicholas J; Högler, Wolfgang
Abstract : Intravenous pamidronate has been used in the treatment of osteogenesis imperfecta (OI) in children for over 20 years. The more potent zoledronate is an attractive alternative as it is administered less frequently. This study compares the clinical efficacy of intravenous pamidronate (1.5 mg/kg/day over 2 days, every 3 months) versus zoledronate (0.05 mg/kg/dose every 6 months) in 40 children (20 per group) with mild to moderate OI and the treatment costs of the two drugs in a tertiary centre for children with osteoporosis. Lumbar spine bone mineral density and fracture rate did not differ between drug groups following 1 and 2 years of treatment, respectively. Total cost per treatment course per patient was £1157 for pamidronate and £498 for zoledronate. Therefore, zoledronate is a considerably cheaper alternative to pamidronate with comparable efficacy, resulting in substantial annual savings for healthcare providers and a more convenient option for patients due to fewer hospital visits.